Differences of Sexual satisfaction, dysfunctional relationship beliefs and dyadic adjustment among addicts under methadone treatment and withdrawal applicants - Arani, Soheila Shaei; Shandy, Fatemeh Azartash (International Journal of Psychosocial Rehabilitation, 2020)
PURPOSE: This study was conducted to compare withdrawal applicants (untreated) with patients who were under methadone maintenance treatment for at least 6-month to investigate sexual satisfaction, dyadic adjustment and dysfunctional relationship beliefs. METHODS: The population included addicts referring to addiction treatment centers in Shiraz and their wives in 2013. A sample of 74 addicts admitted to these centers, together with their spouses participated in the study. Data was collected through questionnaires of spanier revised dyadic adjustment, Larson sexual satisfaction, and relationship beliefs inventory (RBI). Then, the data was analyzed via t-tests. RESULTS: The partner’s dysfunctional relationship beliefs were observed more in the drug abusers (untreated) group than the group under methadone maintenance treatment. Also differences in destructive disagreement and sexual perfectionism as two subscales of dysfunctional relationship beliefs, as well as differences in agreement and satisfaction as two subscales of dyadic adjustment were significant between the groups. DISCUSSION: According to the results, it is essential to hold long-term courses for training relationship techniques to couples and to use special techniques for correction of cognitive errors among addicts.